En Bloc Resection of Bladder Tumor—Is It the Way Forward? - Fankhauser, Christian Daniel; Wettstein, Marian Severin; Afferi, Luca; Grossmann, Nico Christian; Mostafid, Hugh (Frontiers in Surgery, 2021)
Transurethral resection of bladder tumors (TURBT) represents the cornerstone in diagnosis and treatment of bladder cancer but recurrence is observed in up to 80% and over- or understaging with TURBT is common. A more recent development to overcome these limitations represents en-bloc resection of bladder tumors (ERBT) which offers several advantages over TURBT. In this report, we briefly review studies assessing outcomes of bladder cancer patients undergoing ERBT. Most randomised and non-randomised trial demonstrate improvement in clinical outcomes for ERBT over TURBT, however more pathological and translational studies are warranted.